Dapodik Application-Based Management Information System at The Malinau Regency Education Office (Teacher Certification Study) - Aini, Sarifa; Rulinawaty, Rulinawaty; Wijaya, Andi (Ideas Publishing, 2024)
The implementation of management information systems based on the Dapodik Application System at the Malinau District Education Office is a challenge considering that it is located in a border area and there are still many schools that are not reached by the internet or electricity. This research discusses the implementation of the management information system based on the dapodik application system in the education office of Malinau district (teacher certification study) and the inhibiting factors in the implementation of the system. The research method used is descriptive qualitative. The inhibiting factors of the implementation are limited internet network in some schools, delays in data inputting or updating school data and/or teachers who make changes to certification data, electricity is still limited to some education units, schools and teachers still have difficulties in using the dapodik application, and changes in school dapodik operators so that they must be re-socialiser.